Practical approach to electromyography : an illustrated guide for clinicians - Siao, Peter (Demos Medical, 2011)
Practical Approach to Electromyography is a pictorial guide to performing and interpreting EMG studies. This step-by-step manual contains tips for working up clinical problems typically encountered in the EMG laboratory and highlights technical aspects and potential pitfalls of sensory and motor nerve conduction studies. Hundreds of photographs and drawings illustrate proper placements of recording and stimulation electrodes and insertion of needle electrodes into the various muscles. The authors also provide sets of normal values and instruction on how to write and interprete an EMG report. Practical Approach to Electromyography is a visual practical reference for both novices and experienced electromyographers and belongs in every EMG laboratory.